IFRS for SMEs: Eine Alternative für den Einzelabschluss aus Sicht des deutschen Mittelstandes? - Henselmann, Klaus; Klein, Martin; Wiese, Maren (2010)
The objective of the IFRS for SMEs is to provide SMEs an attractive accounting alternative according to international standards. The paper analyses the differences compared to the German-GAAP and highlights the consequences for medium-sized entities in Germany. – Accounting ; full IFRS ; IFRS ; IFRS for SMEs ; non-listed companies ; small and medium-sized entities (SMEs)